Efforts to Protect Victims of Domestic Violence in Divorce Cases in Court - Fathiyah, Shofa; Santiago, Faisal (Publikasi Indonesia, 2024)
The number of domestic violence cases continues to increase every year. The majority of the victims of violence are women. The purpose of this study is to determine the protection in the form of fulfilling the rights of domestic violence victims in divorce cases to achieve justice, certainty, and utility. This research uses a qualitative method by employing normative research that examines primary, secondary, and tertiary legal materials and utilizes descriptive analysis. The theory used is the theory of legal objectives, namely justice, certainty, and utility. This study analyzes efforts to protect victims by the domestic violence eradication law. Based on the results of this research, efforts in the divorce process include filing for protection and fulfilling rights, and the implementation of fulfilling the rights of domestic violence victims after divorce is not oriented towards legal certainty and utility as stipulated by the law.